THE USE OF COHESION DEVICES OF THE STUDENTS’ ESSAY IN WRITING CLASS OF ENGLISH DEPARTMENT - Fristi Arfiawati (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This research entitled The Use of Cohesion Devices of the Students’ Essay in Writing Class of English Department applied the theory from Halliday & Hasan (1976).  The purpose is to investigate the type of cohesion device which is used by the students of English Department in writing the essay of the writing class. This study applied qualitative descriptive method in analizing the data. Furthermore, the data were gained by collecting writing task of the students in writing class which has already learned about the type of cohesion devices.  The finding showed that there were  41% the use of reference, 2.6% the use of substitution, 56.4 % the use of conjunction, and 0% the use of ellipsis. In addition, the most dominant usage of cohesion devices types is conjunction.  Thus, the result showed that the use and the variety of cohesion devices is still low. The students still need to learn more about cohesion devices in order to have a good pieces of writing.